The Pindaric poetry of Cruz e Silva and the Neoclassical revival among Lusitanian national heroes - Fonseca, Rui Carlos (2016)
António Dinis da Cruz e Silva, member of Arcádia Lusitana, the literary academy he helped to found, introduced the Pindaric ode to the Portuguese literature of the neoclassical period (18th century). This poet imitates the triadic form and the mythological nature of Pindar’s encomiastic poetry, in order to celebrate the deeds of reputed historical figures from the national context, such as sailors, captains, politicians, and even the king himself. As in Pindar’s poetry, the mythological excursus holds an important part in Cruz e Silva’s Pindaric poetry. Winners of athletic games are acclaimed through allusion to the ancient heroes. Likewise, the heroes of the Portuguese history see themselves turned into immortals, since their deeds are reported as comparatively greater than those of Homeric warriors. Among the 44 Cruz e Silva’s Pindaric odes, 18 rewrite the myth of the Trojan War, from its beginnings with Eris (Odes I-II) to its outcome with the imperishable fame of the most conspicuous Homeric fighters (Ode XLII). These 18 compositions (re)tell, in a neoclassical style, the main scenes and themes of the Iliad and Odyssey, alluding directly to their heroes’ deeds. Achilles’ wrath and Hector’s death are topics repeatedly brought up in Cruz e Silva’s Pindaric poetry as models of courage and patriotism for national heroes. This chapter offers a discussion of Cruz e Silva’s neoclassical representation of the Trojan War. To this effect, an interdisciplinary approach is adopted, showing how the Portuguese poet handles the mythological material from Homer and Pindar. In this way, he initiated in 18th-century Portuguese literature a new literary genre, the Pindaric ode. By dealing with Poetry and History, Cruz e Silva perpetuated the life and fame of national heroes long after their deaths.